Rancang Bangun Sistem Informasi Pencatatan Alat Laboratorium IPA di SMA Negeri 1 Mutiara, Kabupaten Pidie - Mahdalena; Yasir, Muhammad; Idwan, Harry (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This study aims to design and develop an information system for the inventory management of science laboratory equipment at SMA Negeri 1 Mutiara, Pidie Regency. The current manual management of laboratory equipment is prone to errors in recording and inventory control. Therefore, the developed information system is expected to speed up and simplify the process of recording, borrowing, and returning equipment more efficiently. The system development method used is the prototyping method, with data collection through interviews, observations, and documentation. The system testing results show that the web-based application developed successfully facilitates the management of laboratory equipment, reduces human errors, and enhances operational efficiency. This system allows the laboratory staff to automatically record equipment, with integrated features for borrowing and returning equipment. The implementation of this information system is expected to make the management of laboratory equipment at SMA Negeri 1 Mutiara more transparent, organized, and effective.